2006
DOI: 10.1245/s10434-006-9106-9
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography and Fine-needle Aspiration Cytology in the Preoperative Evaluation of Melanoma Patients Eligible for Sentinel Node Biopsy

Abstract: In our hands, the sensitivity and specificity of preoperative ultrasonography to detect lymph node involvement in patients with melanoma are 34% and 87%, respectively. In combination with FNAC, this is 4.7% and 100%, respectively. This yield is insufficient for this technique to be used as a routine diagnostic tool in the selection of patients eligible for sentinel node biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
37
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 23 publications
0
37
2
1
Order By: Relevance
“…When compared to the literature, the sensitivity in our hands (51%) is significantly higher than previously reported rates, which differ from 4% to 39% [24][25][26][27][28][29]. In these relatively small series, Starritt et that high-resolution ultrasound (HRUS) yielded a sensitivity of 12% (2/17) [28].…”
Section: Discussioncontrasting
confidence: 68%
“…When compared to the literature, the sensitivity in our hands (51%) is significantly higher than previously reported rates, which differ from 4% to 39% [24][25][26][27][28][29]. In these relatively small series, Starritt et that high-resolution ultrasound (HRUS) yielded a sensitivity of 12% (2/17) [28].…”
Section: Discussioncontrasting
confidence: 68%
“…Our study and those done by Rossi, Hocevar, van Rijk and Sibon were performed without lymphoscintigraphy targeting of the draining nodal basin, whereas the studies by Voit and Sanki were performed after lymphoscintigraphy. [15, 16, 18, 4143] It is difficult to compare these studies directly since targeting draining nodal basins may affect sensitivity and specificity. Furthermore, the patient and tumor characteristics also vary and can influence the results.…”
Section: Discussionmentioning
confidence: 99%
“…According to studies done by Voit et al ,17 combined US and FNAC provides important information prior to SLNB in that both procedures identify metastases in the lymph nodes (sensitivity >80%). Although, rare studies have reported very low sensitivity which is attributed to tiny and necrotic lesions,19 20 most authors have emphasised the importance of USG-guided FNAC in the detection of sentinel lymph node metastasis 17–19 21. With a positive cytology of the sentinel node, surgeons can proceed with the direct radical lymph node dissection in patients with melanoma; thereby preventing unnecessary anaesthesia and surgical management as well reduce costs 17.…”
Section: Discussionmentioning
confidence: 99%